Identification of alcohol abuse and transition from long-term unemployment to disability pension. Issue 5 (July 2015) - Nurmela, Kirsti; Heikkinen, Virpi; Hokkanen, Risto; Ylinen, Aarne; Uitti, Jukka; Mattila, Aino; Joukamaa, Matti; Virtanen, Pekka
Aims: The aim of the study was to reveal potential gaps and inconsistencies in the identification of alcohol abuse in health care and in employment services and to analyse the granting of disability pensions with respect to the alcohol abuse identification pattern. Methods : The material consisted of documentary information on 505 long-term unemployed subjects with low employability sent to the development project entitled 'Eligibility for a Disability Pension' in 2001–2006 in Finland. The dichotomous variables 'Alcohol abuse identified in employment services' and 'Alcohol abuse identified in health care' were cross-tabulated to obtain a four-class variable 'Alcohol abuse identification pattern'. Logistic regression analyses were conducted to ascertain the association of alcohol abuse identification pattern with the granting of disability pensions. Results : Alcohol abuse was detected by both health care and employment services in 47% of those identified as abusers (41% of examinees). Each service systems also identified cases that the other did not. When alcohol abuse was identified in health care only, the OR for a disability pension being granted was 2.8 (95% CI 1.5–5.2) compared with applicants without identified alcohol abuse. The result remained the same and statistically significant after adjusting for confounders. Conclusions : Alcohol abuse identified in health care was positively associated with the granting of a disability pension. Closer co-operation between employment services and health care could help to identify those long-term unemployed individuals with impaired work ability in need of thorough medical examination.